2023
DOI: 10.1002/smll.202305054
|View full text |Cite
|
Sign up to set email alerts
|

Composition‐Property Relations for GAxFAyMA1‐xyPbI3 Perovskites

Fernando Brondani Minussi,
Rogério Marcos Silva,
Eudes Borges Araújo

Abstract: Halide perovskites are materials for diverse optoelectronic applications owing to a combination of factors, including their compositional flexibility. A major source of this diversity of compositions comes from the use of mixed organic cations in the A‐site of such compounds to form solid solutions. Many organic cations are possible for this purpose. Although significant progress is made over years of intensive research, the determination of systematic relationships between the compositions and properties of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…In this case, for compositions with high initial GA + concentrations, a smaller degradation extent would be required to reach local GA + supersaturation and trigger GAPbI 3 segregation. Also, it must be considered that the higher the concentration of GA + , the greater the mitigation of ion transport 64,65 therefore, the more difficult (slow) the redistribution of ions would be, translating into the local concentration of GA + increasing quicker. Given this plausible scenario, we studied the thermal degradation behavior of GA x MA 1Àx PbI 3 compositions with x up to 0.20.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, for compositions with high initial GA + concentrations, a smaller degradation extent would be required to reach local GA + supersaturation and trigger GAPbI 3 segregation. Also, it must be considered that the higher the concentration of GA + , the greater the mitigation of ion transport 64,65 therefore, the more difficult (slow) the redistribution of ions would be, translating into the local concentration of GA + increasing quicker. Given this plausible scenario, we studied the thermal degradation behavior of GA x MA 1Àx PbI 3 compositions with x up to 0.20.…”
Section: Resultsmentioning
confidence: 99%
“…, CsPbI 3 's metastable polymorphs). 1,2 There are more reports of single-phase inorganic HEAHP (Table S4, ESI†) 71–219 and hybrid organic–inorganic HEAHP (Table S5, ESI†), 220–285 but more investigation into single-phase boundaries is needed to confirm the broadscale applicability of UCV for screening HEAHP.…”
Section: Resultsmentioning
confidence: 99%
“…42,73,74 In previous studies, it has been found that the advantages of packaged crystalline films that can be modulated by a variety of compositions come along with challenges. 16,75,76 In recent record-breaking studies, multicomponent hybrid perovskites have come to the fore. 77 For example, the introduction of A-site cations with different radius can improve the efficiency of the device but at the same time may also bring more surface defects.…”
Section: The Importance Of Interface Engineeringmentioning
confidence: 99%